K.J. Aiyer's judicial dictionary : a complete law lexicon - Aiyar, Krishna Jagadisa, 1885- (New Delhi : LexisNexis Butterworths, 1980)
Dictionary of terminology mostly used in Indian courtrooms.
Keywords: Law -- India -- Dictionaries